Not Yet Up to Standard : The Legacy of Two Decades of Private, Governmental, and Donor Effects to Promote Ugandan Horticultural Exports - Rios, Luz Diaz (World Bank, Washington, DC, 2017)
The relative prosperity enjoyed by Uganda during the 1960s, based largely on the traditional exports of coffee, tea, cotton, and tobacco, was eroded by a devastating civil war over the period 1971 to 1985. The paper is based upon interviews with selected respondents, including government authorities, exporting companies, donors, and practitioner organizations, carried out in 2007 and 2008. The paper is divided into four sections. Section one provides a brief historical perspective on the emergence of the Ugandan fruit and vegetable export industry and examines the role played by different government and donor initiatives in the initial shaping of the sector, between the late 1980s and late 1990s. Section two highlights the strategic commercial approaches adopted by Ugandan exporting companies and farmers during the 2000s in response to past performance and in the face of evolving regulatory and market requirements, especially in the European Union. Section three examines the rationale for, means of support of, and apparent efficacy of a range of recent programs seeking to improve or sustain the competitiveness of Uganda's fruit and vegetable exports via improved compliance with regulatory or private standards. Lessons are drawn from this experience. Section four provides a brief set of general conclusions.